Profile of Critical Thinking Skills of Class VIII Students at SMPN Bulukumba in Learning Science Material on the Human Respiratory System - Haq, Amalia; Insih Wilujeng; Laifa Rahmawati (BIOEDUKASI: Jurnal Biologi dan Pembelajarannya, 2025)
This study aims to assess and improve students' critical thinking skills in science education, specifically focusing on the human respiratory system. The research was conducted with grade VIII students at SMPN 31 Bulukumba, using a set of 10 multiple-choice questions developed based on the critical thinking skill indicators outlined by Facione (2020), including interpretation, analysis, evaluation, inference, and explanation. The results show that students' critical thinking skills were generally in the moderate category, with the highest scores in the evaluation indicator and the lowest scores in the interpretation and inference indicators. The study suggests that the use of Problem-Based Learning (PBL), supported by video-based learning, inquiry-based methods, and tools like Canva, can significantly enhance students' critical thinking abilities. Additionally, the integration of visual aids such as 3D animations can help students better understand complex concepts. The study emphasizes the importance of selecting effective teaching strategies that foster higher-order thinking skills and improve students' performance in interpreting, analyzing, and explaining scientific concepts. These strategies can enhance students' critical thinking skills, equipping them for the challenges of the 21st century.